The impact of beak tissue sloughing and beak shape variation on the behavior and welfare of infrared beak-treated layer pullets and hens. (9th May 2019) - Struthers, S; Classen, H L; Gomis, S; Crowe, T G; Schwean-Lardner, K
ABSTRACT: This research examined how infrared beak treatment (IRBT), sloughing of the treated beak tissue, and the variations in beak shape that can occur post-IRBT impact the welfare and mortality of Lohmann LSL-Lite (LW) and Lohmann Brown (LB) pullets and hens. Two experiments were conducted and birds for both experiments were treated on the day of hatch. IRBT equipment settings were adjusted to create 4 specific beak shapes: shovel (SHV), step (STP), standard (STAN), and an untreated sham control (C). Experiment 1 pullets (n = 80 per strain) were reared in bioassay cages from 1 to 29 D of age (4 replicates per treatment). Data collected included time and presence of beak sloughing, pecking force, behavioral expression, and mortality. Experiment 2 pullets (n = 320 per strain) were reared in floor pens from 1 D to 18 wk of age (2 replicates per treatment) and then conventional cages from 18 to 60 wk of age (6 replicates per treatment). Data collected for Experiment 2 included behavioral expression, feather cover, comb damage, and mortality. Data were analyzed using PROC MIXED (SAS® 9.4) with Tukey's test to separate means. Differences were significant when P ≤ 0.05. IRBT and sloughing had no effect on pecking force or mortality throughout rearing. The variations in post-IRBT beak shape had minor effects on behavior. During rearing, STAN pullets were more active than C pullets but STP and STAN pullets performed less exploratory pecking. During the laying period, SHV and STP hens preened more than C hens. The IRBT treatments, regardless of beak shape, reduced feather loss, comb damage, and cannibalism-related mortality during the laying period. Overall, the results indicate that LW and LB pullets and hens can cope with the change in beak shape that occurs with IRBT, and that welfare is not negatively impacted if some variation in beak shape occurs.